Obstetric and perinatal risks in 4601 singletons and 884 twins conceived after fresh blastocyst transfers: a Nordic study from the CoNARTaS group. Issue 4 (15th April 2020) - Spangmose, A L; Ginström Ernstad, E; Malchau, S; Forman, J; Tiitinen, A; Gissler, M; Opdahl, S; Romundstad, L B; Bergh, C; Wennerholm, U B; Henningsen, A A; Pinborg, A
Abstract: Study question: Are obstetric and perinatal outcomes in pregnancies after fresh blastocyst transfer (BT) comparable with those born after fresh cleavage stage transfer (CT) and spontaneous conception (SC)? Summary answer: Fresh BT is associated with a higher risk of placental and perinatal complications. What is known already: BT optimizes the selection of top-quality embryos and increases pregnancy and live birth rates per transfer compared to CT. However, concerns have been raised as extended culture duration may increase obstetric complications and impair perinatal outcomes. Previous studies have shown a higher risk of preterm birth (PTB) among infants born after BT compared with CT. Pregnancies after BT are also prone to a higher risk of same-sex twins after single embryo transfer (SET). Study design, size, duration: A retrospective register-based cohort study used data from Denmark, Norway and Sweden including three cohorts: 56 557 singletons and 16 315 twins born after fresh IVF/ICSI cycles and 2 808 323 SC singletons in Denmark (birth years 1997–2014), Norway (2010–2015) and Sweden (2002–2015). Of the fresh IVF/ICSI singletons, 4601 were born after BT and 51 956 after CT. The twin cohort consisted of 884 fresh IVF/ICSI children born after BT and 15 431 fresh IVF/ICSI children born after CT. Participants/materials, setting, methods: Data were obtained from a large Nordic cohort of children born after ART and SC initiated by the Committee of Nordic ART and Safety (CoNARTaS). The CoNARTaS cohort was established by cross-linking National ART-, Medical Birth-, and National Patients Registers using the unique personal identification number, allocated to every citizen in the Nordic countries. Obstetric and perinatal outcomes after BT, CT and SC were compared using logistic regression analysis. For perinatal outcomes, we calculated gestational age based on the date of oocyte pick-up (OPU) and in sensitivity analyses on data from Denmark and Norway, we also calculated gestational age based on the second-trimester ultrasonography (US) scan. Risk of pregnancies with same-sex twins after SET was used as a proxy for risk of monozygotic twins. Adjustments were made for child's sex, birth year, parity (0 or >1), maternal age, body mass index, smoking, educational level, fertilization method (IVF/ICSI), the number of aspirated oocytes, SET and country. Information on educational level and the number of aspirated oocytes was not available for Norway. Children born after frozen embryo transfer were not included. The birth cohorts were restricted according to the year in which BT was introduced in the different countries. Main results and the role of chance: A higher risk of placenta previa was found in singleton pregnancies after BT compared with CT (adjusted odds ratio [aOR] 2.11 [95% CI 1.76; 2.52]). Singletons born after BT had a higher risk of PTB (aOR 1.14 [95% CI 1.01; 1.29]) compared with CT singletons, when estimated based on OPU. Furthermore, an altered male/female ratio (aOR 1.13 [95% CI 1.06; 1.21]) with more males following BT compared with CT was seen. Risk of same-sex twins after SET was higher after single BT compared with single CT (aOR 1.94 [95% CI 1.42; 2.60]). Limitations, reasons for caution: Residual confounding cannot be excluded, in particular related to duration and cause of infertility that we could not adjust for due to lack of reliable data. Wider implications of the findings: Extended embryo culture to the blastocyst stage has the potential to compromise obstetric and perinatal outcomes in fresh cycles. These results are important since an increasing number of IVF/ICSI treatments are performed as BT. Study funding/competing INTEREST(S): NORDFORSK (project no: 71450). The Research Fund of Rigshospitalet, Copenhagen University Hospital. ReproUnion Collaborative study, co-financed by the European Union, Interreg V ÖKS. Grants from Swedish state under the agreement between the Swedish government and the county councils, the ALF-agreement (LUA/ALF 70940), Hjalmar Svensson Research Foundation. The Research Council of Norway through its Centres of Excellence funding scheme, project number 262700. None of the authors has any conflicts of interests to declare regarding this study. Trial registration number: ISRCTN11780826.